Quantifying in international conflict: the linkage approach - Abdelkrim KIBECHE (Revue des Sciences Humaines)
The evolution of international relations has introduced a development in the subject and in the method itself. For instance, the use of quantitative method could improve the international relations science, especially in the study of international conflict.